2016
DOI: 10.1080/11263504.2016.1174169
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic ozone exposure temporarily affects seed germination in alpine plants

Abstract: This study was the first to investigate the direct effects of anomalous concentrations of ozone mediated by summer heat waves on seed germination in alpine plants. During germination, the seeds were exposed to three peaks of O 3 concentration (125ppb for 5 and 10 days; 185ppb for 5 days), derived from measurements taken close to the species growing site. High O 3 concentration delayed the First Germination Time, increased the Mean Germination Time and reduced the Germination Percentage during and immediately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…On the other hand, ozone has been used to enhance seed germination [153] or improve fruit quality [154]. Ozone seemingly has an ambivalent role that is dependent on the concentration and length of treatment [155] as it is the case for many other treatments i.e., hormone, nanoparticles, heat. The authors mentioned that there is a variable response to the same ozone treatment based on the species and it is weak and transient.…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
“…On the other hand, ozone has been used to enhance seed germination [153] or improve fruit quality [154]. Ozone seemingly has an ambivalent role that is dependent on the concentration and length of treatment [155] as it is the case for many other treatments i.e., hormone, nanoparticles, heat. The authors mentioned that there is a variable response to the same ozone treatment based on the species and it is weak and transient.…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
“…Based on the natural occurrence of ozone peaks of about 100 ppb(The Royal Society, 2008), the use of ozone concentrations between 100 and 130 ppb is common in plant experimental eco-physiology (seeAbeli et al (2017),Khaling et al (2015),Ueno et al (2016)). The contrasting levels of ozone were generated by a spark discharge-typeozone generator (OZ5000, Dobzono, AR), with the concentration of ozone within each chamber recorded by monitoring the 254 nm absorbance on an API-Teledyne model 450 ozone monitor (Teledyne Advanced Pollution Instrumentation Inc., USA).…”
mentioning
confidence: 99%
“…To some extent, plants are capable of controlling the ozone-induced oxidative stress by activating enzymatic and non-enzymatic antioxidant machinery (Iriti & Faoro, 2008;Menéndez, Romero, Folcia, & Martínez-Ghersa, 2009). Thus, determined by the type of exposure and concentration, ozone can generate context-dependent effects with detectable/undetectable and positive/negative impacts on plant performance [e.g., Abeli et al (2017); Bermejo et al (2003); Menéndez et al (2017); Ueno et al (2016); Ueno, Gundel, Seal, Ghersa, and Martínez-Ghersa (2020)]. TGE, which is the source of phenotypic variation expressed in the progeny from plants experiencing different environmental conditions (Burton & Metcalfe, 2014;Donohue, 2009;Herman & Sultan, 2011), has been intensively reviewed as a mechanism for plants to cope with biotic and abiotic factors of stress (Yin et al, 2019).…”
mentioning
confidence: 99%
“…Most ozone studies analyse its effects on plant growth or crop yield but are not necessarily designed to determine critical periods of sensitivity. Despite it being shown that ozone exposure during germination can cause seed mortality (Abeli et al, 2017), no studies have evaluated the ozone-mediated TGEs during progeny plant establishment under similar environmental conditions (i.e., ozone exposure).…”
mentioning
confidence: 99%